FUNGSI FESTIVAL LEGU GAM MOLOKU KIE RAHA BAGI MASYARAKAT KOTA TERNATE - Ismail, Farda Yushana (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The aim of this study is to observe the functions Legu Gam Moloku Kie Raha festival for peoplein ternate. Sultanate of ternate or the kingdom of gapi is one of the four Islamic kongdom in north malukuand the oldest Islamic kingdom in nusantara. The power sultanate of ternate can be seen since the first sultanof 1257-1277 has given the traditional authority and celebration or Dorogam. Dorogam is a celebration ofsociety. The celebration Dorogam held at right time in Moloku Kie Raha. In 2002 Dorogam has changed thename Legu Gam festival or celebration of society.The methodology used was qualitative research. Result this study shows that Legu Gam Moloku KieRaha festival described of good relationship between the sultanate and the people in ternate. Legu Gamfestival has become a symbol for Moloku Kie Raha and has become the most awaited festival by the peoplein ternate. Legu Gam festival is functional structural festival and has several function. The festival has beenprepared in a form a moment the function of religion give thank to god and pray for sultan mudaffar syah’sbirthday. Art preserving performances of traditional dances, music and folk songs, social cultural educationin form of activity-ngongare jojaru, promotion of creative economy as well as to support the budget ternate inPAD.Keywords : Function, Legu Gam Moloku Kie Raha Festival, Ternate.